Re-delimiting oversummering regions of Puccinia striiformis f. sp. tritici in China - Jiguang Zhang; Yuxiang Li; Di Liu; Junjie Zhang; Zhibo Zhang; Qiang Yao; Xiangming Xu; Xiaoping Hu (Phytopathology Research)
Abstract Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most important diseases on wheat, causing severe yield losses. The pathogen can only survive the summer in the cooler areas of northern and western regions in China. Compared to the main wheat-growing region, the oversummering region is relatively small. Therefore, managing stripe rust in the oversummering region is crucial for controlling the disease nationwide. In this study, we conducted experiments to determine the survival of the predominant Pst races in China under high temperatures and used the data to predict potential Pst oversummering regions. The predominant races (CYR32, CYR33, and CYR34) were able to survive and reproduce at an average temperature of up to 27 °C. Disease incidence and the number of uredinia decreased with increasing temperatures of 24–27 °C during incubation. The results from re-delimiting oversummering regions suggested that Pst is able to oversummer in the east of Gansu province and the south of Shanxi province, which were previously considered unsuitable for Pst oversummering. Based on the present study, the east of Inner Mongolia and north of Heilongjiang could provide the oversummering condition for Pst. Three major oversummering regions, the Liupan Mountain range, the highlands in the south of Gansu province, and the east of Qinghai province were identified. The results should be useful for adjusting strategies to manage stripe rust in China.